Effects of seed treatment of cowpea bean Vigna unguiculata L. on the management of vascular wilt caused by Scleroctium rolfsii - campo arana, Rodrigo (2023)
The cowpea bean is a legume of economic importance for small producers in the Caribbean, Colombia; however, grain production is affected by MV vascular wilt, caused by Scleroctium rolsii, causing losses of up to 50 %. The objective of the research was to evaluate the effect of seed treatment in the management of MV. Two experiments were established, the first one was done in the laboratory, determining the active ingredient and dose that does not affect the emergence and development of the seedlings. The second was carried out in a mesh house, where the seeds were treated with the molecules and the best dose identified in the first experiment. The second experiment was established with the Caupicor 50 variety, under a completely randomized design with four repetitions. The treatments evaluated were the following: T0: absolute control, T1: Calcium nitrate (1.0 g l-1), T2: Azoxystrobin + Difenoconazole (1.0 cc l-1); T3: Trichoderma harzianum, (3.0 g Kg-1); T4: Benomyl (2.0 g Kg-1); T5: Carboxim + Thiram (2.0 g Kg-1); T6: potassium phosphite (2.0 g L-1) and T7: negative control, unprotected seeds. The treated bean seeds will be sown in disinfected soil and inoculated with a strain of Scleroctium folfsii. Every four days evaluations of incidence, severity and height were carried out. The most efficient treatments in the management of MV were T2, T3 and T5; however, T2= Azoxystrobin+difecobazol affected seedling emergence.